2021
DOI: 10.1055/s-0041-1739297
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal Diagnosis of Parapagus Conjoined Twins: 3D Virtual and 3D Physical Models

Abstract: Conjoined twins (CTs) are a rare complication from monochorionic and monoamniotic twin pregnancies. We describe the use of 3D technologies, including 3D virtual and 3D physical models on prenatal evaluation of one parapagus CT. A 16-year-old G1P0 woman was referred for fetal magnetic resonance imaging (MRI) anatomical evaluation of a CT at 28 weeks of gestation. 3D images of the fetal surface were generated by the software during the examination for spatial comprehension of the relationship between the fetal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The percentage of studies that addressed the use of magnetic resonance imaging for the evaluation of fetal brain alterations was 29.16% and the articles that presented studies specifically on the gestational consequences of Zika Virus infection corresponded to 12.50% of the total number of studies analyzed. Evaluation of the fetal skeleton [4] Ventriculomegaly [15] Changes in the development of the spine and spinal cord [18] COVID-19 [11] Preeclampsia and brain development [9] Abdominal Malformations (1) [12] Abdominal Malformations (2) [21] Oral teratoma [19] Brain Measurements / Uterine Growth Restriction [20] Hydatidiform spring [22] Brain malformations caused by Zika Virus [14] Placental changes [6] 3D Reconstructions Prototypes [23] 22 Microcephaly related to congenital Zika virus infection [24] 23 Changes in the Central Nervous System (microcephaly) related to congenital Zika virus infection [25] It was observed that 8.34% of the articles discussed placental problems, malformations and uterine pathologies, abdominal malformations, head, and neck diseases, in addition to 3D prototyping. Still, 4.16% of the studies studied non-obstetric indications for maternal MRI, hydatidiform mole, fetal skeletal structure, in addition to alterations in the development of the fetal spine and spinal cord (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The percentage of studies that addressed the use of magnetic resonance imaging for the evaluation of fetal brain alterations was 29.16% and the articles that presented studies specifically on the gestational consequences of Zika Virus infection corresponded to 12.50% of the total number of studies analyzed. Evaluation of the fetal skeleton [4] Ventriculomegaly [15] Changes in the development of the spine and spinal cord [18] COVID-19 [11] Preeclampsia and brain development [9] Abdominal Malformations (1) [12] Abdominal Malformations (2) [21] Oral teratoma [19] Brain Measurements / Uterine Growth Restriction [20] Hydatidiform spring [22] Brain malformations caused by Zika Virus [14] Placental changes [6] 3D Reconstructions Prototypes [23] 22 Microcephaly related to congenital Zika virus infection [24] 23 Changes in the Central Nervous System (microcephaly) related to congenital Zika virus infection [25] It was observed that 8.34% of the articles discussed placental problems, malformations and uterine pathologies, abdominal malformations, head, and neck diseases, in addition to 3D prototyping. Still, 4.16% of the studies studied non-obstetric indications for maternal MRI, hydatidiform mole, fetal skeletal structure, in addition to alterations in the development of the fetal spine and spinal cord (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…3D images of the fetal surface are generated by software during imaging tests for spatial understanding of the relationship between the fetal parts. 3D technologies are an important tool for counseling parents and preparing the multidisciplinary team for childbirth and neonatal care, as well as possible surgical planning for postnatal separation in these cases [14]. Conjoined twins (SG) represent a rare complication of monochorionic and monoamniotic twin pregnancies with an incidence ranging from 1:50,000 to 1:100,000 live births.…”
Section: Use Of Mri For the Diagnosis Of Fetal Abnormalitiesmentioning
confidence: 99%
See 3 more Smart Citations